Kualitas Pelayanan Kesehatan bagi Pasien Badan Penyelenggaraan Jaminan Sosial di Pusat Kesehatan Masyarakat - Febiana Intan Suryati; Aplonia Pala; Tri Anggraini (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
This research is related to the Service Quality of Guarantee Agency Social Services (BPJS) at the Sasi Health Center, KefamenanuCity District, North Central Timor Regency. This research is a qualitative descriptive research. The focus of this research is the quality of health services for patients using BPJS, including (tangibles) physical evidence, reliability, responsiveness, assurance, and empathy. The results of this study indicate that the quality of BPJS services at the Sasi Health Center is quite good in terms of physical evidence that the infrastructure and facilities are sufficient, such as being equipped with waiting rooms that have provided sufficient chairs for patients, delivery rooms, and the availability of several polyclinics to serve patients, the emergency room and etc. The reliability of the medical staff in serving is quite good in terms of the services provided which are sufficient to satisfy the patient. The responsiveness of the officers was quite good as seen from the medical staff who were willing to listen to every complaint from the patient. Guarantees where patients feel comfortable and safe when seeking treatment at the Puskesmas and Puskesmas staff regardless of status in serving patients.